Handover Performance over a Coordinated Contiguous Carrier Aggregation Deployment Scenario in the LTE-Advanced System. (31st August 2014) - Shayea, Ibraheem; Ismail, Mahamod; Nordin, Rosdiadee; Mohamad, Hafizal
Abstract : Although various carrier aggregation deployment scenarios (CADSs) have been introduced in the LTE-Advanced system, issues related to insufficient eNB coverage that leads to low throughput and high drop call have yet to be solved. This paper proposes a new deployment scenario called coordinated contiguous-CADS (CC-CADS), which utilizes two-component carriers (CCs) that operate on two frequencies located in a contiguous band. Each CC antenna is directed to a cell boundary of the other CC. The handover performance of users with various mobility speeds under CC-CADS has been investigated and compared with various deployment scenarios proposed by 3GPP. Simulation results show that the received signal reference power (RSRP) enhancement and performed handover, ping-pong, drop call, and outage probabilities reductions in CC-CADS outperformed the 3GPP's CADSs, thus leading to reduced interruption time, improved spectral efficiency, and seamless handover.